Case Report: A female case of X-linked intellectual disability syndrome type 34 caused by a NONO frameshift variant and literature review - Zhang, Yige; Shi, Xiaoyan; Xiao, Xiao; Yuan, Shuhua; Tang, Jihong (Frontiers in Pediatrics, 2026)
IntroductionTo characterize the clinical and genetic features of a female infant with X-linked intellectual disability syndrome type 34 (MRXS34) caused by a de novo NONO frameshift variant, expanding the understanding of phenotypic mechanisms in females for this X-linked disorder.MethodsRetrospective study of the clinical data of a 10-month-old female infant diagnosed with MRXS34 due to NONO gene variation in June 2024, along with a literature review.ResultsThe proband presented with global developmental delay, relative macrocephaly, generalized hypotonia, cardiac anomalies (patent foramen ovale, moderate tricuspid regurgitation, pulmonary hypertension), etc. Whole-exome sequencing (WES) identified a de novo heterozygous frameshift variant in NONO (NM_007363.5): c.994del (p.Gln322Lysfs*31), confirmed absent in both parents by Sanger sequencing. X-chromosome inactivation (XCI) analysis revealed extreme skewing (99% inactivation of the paternal X-chromosome). Transcriptome sequencing demonstrated significantly reduced NONO expression (TPM = 20.70 vs. controls 52.34 ± 5.81). Literature review encompassing 27 postnatal MRXS34 cases (all male) consistently reported intellectual disability/developmental delay (100%), craniofacial dysmorphism (100%), cardiac defects (91.3%, predominantly left ventricular non-compaction), and corpus callosum abnormalities (85%).DiscussionWe report the first molecularly confirmed female MRXS34 patient. Her full phenotypic manifestation is attributed to the de novo NONO loss-of-function variant combined with extreme non-random XCI. This case critically expands the clinical spectrum of MRXS34, underscores the diagnostic importance of XCI analysis in females with XLID phenotypes, and provides insights into the mechanisms enabling female expression of X-linked recessive disorders.